The development of the effect of peer monitoring on generosity differs among elementary school-age boys and girls - Takagishi, Haruto; Fujii, Takayuki; Koizumi, Michiko; Schug, Joanna; Nakamura, Fumihiko; Kameshima, Shinya (Frontiers in Psychology, 2015)
The purpose of this study was to examine the effect of peer monitoring on generosity in boys and girls aged 6 - 12 years. A total of 120 elementary school students played a one-shot dictator game (DG) with and without peer monitoring by classmates. Children decided how to divide 10 chocolates between themselves and a classmate either in a condition in which their allocations were visible to their peers, or in private. While the effect of peer monitoring on the allocation amount in the DG was clearly present in boys, it was not observed in girls. Furthermore, the effect of peer monitoring in boys appeared at the age of 9 years. These results suggest that the motivation to draw peers’ attention plays a stronger role for older boys than for girls or younger boys. The potential roles of higher-order theory of mind, social roles, and emergence of secondary sex characteristics on the influence of peer monitoring on generosity shown by boys are discussed.